High School Students’ Statistical Literacy Changes in a Flipped Classroom Environment: A Quasi-Experimental Study (Journal of Contemporary Educational Policies and Practices, 2024)
Statistics in the 2018 Vietnam General Education Curriculum for Mathematics is emphasized from Grade 2 to Grade 12, helping develop students’ competences and qualities. However, students still struggle to connect and apply statistical concepts to real-life situations. This study used a flipped classroom model to teach 10th-graders statistics to develop their statistical literacy. Using a quasi-experimental design, we evaluated how the students’ statistical literacy developed as they participated in the flipped classroom. The results show that the flipped classroom improves students’ statistical literacy. All four categories of statistical literacy increased statistically significantly, including graphical displays, measures of central tendency, measures of variability, and using statistical knowledge to solve problems. The results are explained by the opportunities embedded into the program. Time outside of class was used for the students to review content and access new concepts, along with questions to demonstrate their statistical knowledge and reveal shortcomings. The students spent the most of their interaction time in class on activities to understand concepts and applied them to real-life situations. Some lessons learned from the study are discussed.